Being Controlled by Normative Influences: Self-Determination as a Moderator of a Normative Feedback Alcohol Intervention - Neighbors, Clayton (2006)
The objectives of this research were to evaluate the efficacy of computer-delivered personalized normative feedback among heavy drinking college students and to evaluate controlled orientation as a moderator of intervention efficacy. Participants (N = 217) included primarily freshman and sophomore, heavy drinking students who were randomly assigned to receive or not to receive personalized normative feedback immediately following baseline assessment. Perceived norms, number of drinks per week, and alcohol-related problems were the main outcome measures. Controlled orientation was specified as a moderator. At 2-month follow-up, students who received normative feedback reported drinking fewer drinks per week than did students who did not receive feedback, and this reduction was mediated by changes in perceived norms. The intervention also reduced alcohol-related negative consequences among students who were higher in controlled orientation. These results provide further support for computer-delivered personalized normative feedback as an empirically supported brief intervention for heavy drinking college students, and they enhance the understanding of why and for whom normative feedback is effective.